Intermittent fasting reduces glaucomatous damage in an HSP27 autoimmune mouse model - Maler, Dominik L.; Reinehr, Sabrina; Deppe, Leonie; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2026)
BackgroundCurrently, the treatment of glaucoma is limited to reducing intraocular pressure since other involved pathomechanisms are not well understood yet. Evidence points to an immune-mediated component in disease development. For example, elevated antibody levels against heat shock protein 27 (HSP27) were detected in glaucoma patients. In mice, we previously noted glaucoma-like damage after an intravitreal HSP27 injection. Now, we aimed to investigate if intermittent fasting protects from this glaucomatous damage.MethodsCD1 mice were intravitreally injected with HSP27 into one eye. The contralateral eye served as a control. After injections, half of the animals received food ad libitum (no diet). The other half fasted, hence access to food was denied for 24 h at three days per week (diet). The animals were weighed weekly. Retinal thickness was analyzed via optical coherence tomography (OCT) after 4 weeks (n = 7 eyes/group). Via immunohistology, retinal ganglion cells (RGCs), apoptotic cells, macroglia, microglia/macrophages, tumor necrosis factor (TNFα), and interleukin (IL)-1β were analyzed (n = 6 eyes/group). Corresponding markers were examined with RT-qPCR (n = 4 samples/group). In addition, microarray assays were performed from serum samples from mice with diet or with no diet (n = 6 samples/group).ResultsThe weight and OCT measurements revealed no differences between the groups. HSP27 retinas had significantly lower RGC numbers as well as decreased Rbmps mRNA levels compared to controls, while HSP27+diet retinas displayed similar RGC counts as controls. No difference was observed in apoptotic markers. The macroglia+ area was increased in HSP27 tissue, while the HSP27+diet group showed no difference to controls. The number of microglia was not altered after HSP27 injection but was lower in HSP27+diet retinas. Tnfa and Il1b expression levels were downregulated in HSP27+diet samples compared to control as well as HSP27 tissue. Moreover, different pro-inflammatory cytokines, including IL-1β and IL-6, were lower in the serum of diet mice compared to no diet ones.ConclusionIntravitreal injection of HSP27 resulted in RGC loss and was associated with gliosis. In contrast, intermittent fasting conferred neuroprotective effects, likely by modulating neuroinflammatory pathways, and hence protected RGCs from damage. These findings highlight intermittent fasting as a potential adjunctive therapeutic strategy for glaucoma management.